Effect of Soybean Flour on Physico-chemical, Functional, and Rheological Properties of Composite Flour from Rice, Sweet Potato, and Potato - Elisa Julianti,; Herla Rusmarilin,; Ridwansyah,; Era Yusraini, (Tropical Life Sciences Research, 2016)
Three composite flours were prepared by combining rice flour, potato starch, sweet potato flour, soybean flour, and xanthan gum in the ratio of 30: 15: 50: 4.5: 0.5; 30: 15: 45: 9.5: 0.5; and 30: 15: 40: 14.5: 0.5, were analysed for selected physical, chemical, functional, and rheological properties. Fat, protein, ash, and crude fibre content were found to increase with increase in the ratio of soybean flour and decrease in the ratio of sweet potato flour in the mixture. The composite flours were not significantly different in water and oil absorption capacity, swelling power, and baking expansion. There was a tendency for the relative viscosities of the composite flours to increase significantly with increasing proportion of the soybean flour and decreasing proportion of sweet potato flour in the mixture. Pasting viscosity measurements of the composite flours gave maximum (peak) viscosity values ranging from 582.00–668.67 cP. The pasting analysis results indicated increased level of setback and final viscosity, pasting temperature, setback and stability ratio while peak viscosity decreased with increasing proportion of soybean flour and decreasing proportion of sweet potato flour in the mixture.